Advanced low grade serous ovarian cancer: A retrospective analysis of surgical and chemotherapeutic management in two high volume oncological centers - Di Lorenzo, Paolo; Conteduca, Vincenza; Scarpi, Emanuela; Adorni, Marco; Multinu, Francesco; Garbi, Annalisa; Betella, Ilaria; Grassi, Tommaso; Bianchi, Tommaso; Di Martino, Giampaolo; Amadori, Andrea; Maniglio, Paolo; et al. (Frontiers in Oncology, 2022)
Background: Low grade serous ovarian cancer (LGSOC) is a rare entity with a different behavior compared to high grade serous (HGSOC). Due to its general low chemosensitivity, complete cytoreductive surgery with no residual disease is crucial in advanced stage LGSOC. We aimed to evaluate the impact of optimal cytoreduction on survival outcome both at first diagnosis and at recurrence. Methods: We retrospectively studied consecutive patients diagnosed with advanced LGSOCs, who underwent cytoreductive surgery in two oncological Centers from January 1994 to December 2018. Survival curves were estimated by the Kaplan-Meier method and 95% confidence interval (95% CI) were estimated using Greenwood formula. Results: a total of 92 patients were included (median age was 47 years, IQR 35-64). Median overall Survival (OS) was 142.3 months in patients with no residual disease (RD), 86.4 months for RD 1-10 mm and 35.2 months for RD>10 mm (p=0.002). Progression free survival (PFS) was inversely related to RD after primary cytoreductive surgery (RD=0 vs RD =1-10 mm vs RD > 10 mm, p=0.002). On multivariate analysis, RD 1-10 mm (HR=2.30, 95% CI 1.30-4.06, p=0.004), RD >10 mm (HR=3.89, 95% CI 1.92-7.88, p=0.0004), FIGO stage IV (p=0.001) and neoadjuvant chemotherapy (NACT) (p=0.010) were independent predictors of PFS. RD >10 mm (HR=3.13, 95% CI 1.52-6.46, p=0.004), FIGO stage IV (p<0.0001) and NACT (p=0.030) were significantly associated with a lower OS. Conclusions: Optimal cytoreductive surgery improves survival outcomes in advanced stage LGSOCs. When complete debulking is not possible, a RD < 10 mm confers better OS compared to RD > 10 mm in this setting of patients.